Factores de riesgo en pacientes con amenaza de parto pretérmino atendidas en el Hospital Isidro Ayora de Loja ; de agosto a noviembre 2015 - López Márquez, Sandra Beatriz (2016)
This research work deals with risk factors in patients with premature birth at the Isidro Ayora Hospital of Loja, from August to November 2015, where it was considered as main objective: To determine the risk factors that affect in women with premature labor at the Isidro Ayora Hospital of Loja from August to November 2015, also specific objectives are: to determine the frequency of premature labor at the Isidro Ayora hospital of Loja, from August to November 2015. To identify risk pathologies of premature childbirth at the Isidro Ayora hospital of Loja, from August to November 2015; to establish gynecologists-obstetric history of the patients treated at the Isidro Ayora hospital of Loja, from August to November 2015; in addition, a retrospective study as transversal quantitative from 596 treated patients during this period, where 182 patients reflected preterm labor. Besides, Obsevation method was used as well as data collection sheets were used as instruments from medical records of each patient at the Isidro Ayora Hospital of Loja. The results reflected that 32% of patients were admitted to the gynecologists-obstetric service by incidence of preterm labor, meanwhile the pathologies of the premature labor were caused by Urinary tract infections (UTIs) and vaginal infections, whereas gynecologists and obstetric history were first pregnancy patients with an average of two sexual partners. Concluding that the risk factors in patients with preterm labor treated at the hospital Isidro Ayora hospital of Loja during the period were caused by urinary tract infection (UTIs) with the causative agent of Escherichia coli and vaginal infections with Gardenella vaginalis. KEYWORDS: Risk factors, preterm labor (premature labor, premature birth, premature deliver) Revised by: Anderson Fernando Reyes Benitez LICENCIADO EN CIENCIAS DE LA EDUCACION MENCION IDIOMA INGLES Registro: 1008-15-1421365